2023
DOI: 10.1038/s41597-023-02704-z
|View full text |Cite
|
Sign up to set email alerts
|

NONAN GaitPrint: An IMU gait database of healthy young adults

Tyler M. Wiles,
Madhur Mangalam,
Joel H. Sommerfeld
et al.

Abstract: An ongoing thrust of research focused on human gait pertains to identifying individuals based on gait patterns. However, no existing gait database supports modeling efforts to assess gait patterns unique to individuals. Hence, we introduce the Nonlinear Analysis Core (NONAN) GaitPrint database containing whole body kinematics and foot placement during self-paced overground walking on a 200-meter looping indoor track. Noraxon Ultium MotionTM inertial measurement unit (IMU) sensors sampled the motion of 35 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…Twenty-six young adults between the ages 19–35 (12 female, 24.5 ± 2.1 years old, 174.5 ± 7.0 cm tall, weighing 72.3 ± 15.6 kg), 28 middle-aged adults between the ages 36–55 (24 female, 46.4 ± 6.1 years old, 170.5 ± 7.4 cm tall, weighing 80.9 ± 14.6 kg), and 27 older adults greater than 55 years old (12 female, 64.3 ± 6.2 years old, 172.2 ± 9.3 cm tall, weighing 80.6 ± 15.9 kg) were sampled from the NONAN GaitPrint dataset [45] . Each participant came into the lab twice, spread one week apart, to complete 9 walking trials per session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six young adults between the ages 19–35 (12 female, 24.5 ± 2.1 years old, 174.5 ± 7.0 cm tall, weighing 72.3 ± 15.6 kg), 28 middle-aged adults between the ages 36–55 (24 female, 46.4 ± 6.1 years old, 170.5 ± 7.4 cm tall, weighing 80.9 ± 14.6 kg), and 27 older adults greater than 55 years old (12 female, 64.3 ± 6.2 years old, 172.2 ± 9.3 cm tall, weighing 80.6 ± 15.9 kg) were sampled from the NONAN GaitPrint dataset [45] . Each participant came into the lab twice, spread one week apart, to complete 9 walking trials per session.…”
Section: Methodsmentioning
confidence: 99%
“…All participant data, including height, weight, anthropometrics, trial details, as well as kinematic features, can be found in the supplementary material . Kinematic time series for the young adults are also published elsewhere, and the data from the middle and older adults soon to follow [45] .
Fig.
…”
Section: Methodsmentioning
confidence: 99%